2016
DOI: 10.1136/postgradmedj-2016-134552
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted D-dimer excludes pulmonary embolism and reduces unnecessary radiation exposure in older adults: retrospective study

Abstract: Background: Patients in whom a diagnosis of pulmonary embolism (PE) is suspected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
(20 reference statements)
6
14
0
Order By: Relevance
“…We selected patients for inclusion if they had presented as an emergency and had both D-dimer and CTPA for suspected PE between September 2012 and March 2016 7. From a cohort of 1397 patients with suspected PE we identified 189 whose CTPA was positive for a first PE and for whom an ECG taken at the time of presentation was available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected patients for inclusion if they had presented as an emergency and had both D-dimer and CTPA for suspected PE between September 2012 and March 2016 7. From a cohort of 1397 patients with suspected PE we identified 189 whose CTPA was positive for a first PE and for whom an ECG taken at the time of presentation was available.…”
Section: Methodsmentioning
confidence: 99%
“…The most common presenting symptoms are dyspnoea and pleuritic pain but both may be absent even in patients with large clot load 6. Clinical probability scores and D-dimer are recommended in order to determine which patients should have CT pulmonary angiography (CTPA) but it is well recognised that patients with low probability scores can have PE with large clot load6 while D-dimer has low specificity for PE and is best regarded as a rule-out test 7…”
Section: Introductionmentioning
confidence: 99%
“…Among the 1324 patients with VTE unlikely (defined using the dichotomized Wells score), the age-adjusted cut-off would have resulted in almost 10% more patients with negative D-dimer, in whom VTE could have been ruled out without imaging and without any false-negative results [20]. Nobes et al evaluated 1000 consecutive patients with suspected PE, who had both D-dimer testing and CTPA [21]. They evaluated the same age-adjusted cut-off (patients age 9 5 ng mL À1 for patients 50 years or older and 250 ng mL À1 for patients younger than 50 years) and found that the combination of unlikely PTP (using the revised Geneva score) and age-adjusted D-dimer would have reduced unnecessary radiation exposure without missing any PE [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nobes et al evaluated 1000 consecutive patients with suspected PE, who had both D-dimer testing and CTPA [21]. They evaluated the same age-adjusted cut-off (patients age 9 5 ng mL À1 for patients 50 years or older and 250 ng mL À1 for patients younger than 50 years) and found that the combination of unlikely PTP (using the revised Geneva score) and age-adjusted D-dimer would have reduced unnecessary radiation exposure without missing any PE [21]. Because three participating centers in the PALLADIO study used D-dimer tests with reduced thresholds, we similarly decided to halve the age-adjusted cut-off in patients older than 50 years, but we kept the conventional fixed threshold for patients up to 50 years, as suggested by a previous laboratory study [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that age-adjusted ddimer cut-offs have acceptable sensitivity for PE and that their use could avoid a significant proportion of CTPA which carry the risk of adverse effects for patients (such as contrast reaction and contrast nephropathy), often cause inconvenience to patients in terms of an extended ED stay and contribute to reduced ED patient flow by requiring an extended ED stay. 2,5,[7][8][9][10][13][14][15][16] Age-adjusted d-dimer cut-offs are intended to be used in conjunction with a clinical risk score to identify a group of patients in whom PE is unlikely and therefore further imaging can be avoided. There are sparse data comparing the performance of age-adjusted d-dimer cut-offs with the various risk scores in common use.…”
Section: Discussionmentioning
confidence: 99%